Matching between dietary preferences and digestive capacity in passerine birds - Kohl, Kevin (My University, 2009)
It has been argued that evolutionary shifts in diet preferences are paired with changes in digestive physiology, including digestive enzyme activities. For example, a previous study in birds (Martinez del Rio 1990) found interspecific variation in enzyme activities that matched species? feeding guilds (frugivore, omnivore, nectivore, etc.). To enhance the findings of this study, we measured the activities of pancreatic and intestinal enzymes in six avian species where diet patterns have been extensively studied. The adaptive modulation hypothesis states that enzyme activities should match the relative levels of substrate present in an animal?s diet so as not to waste biosynthetic energy or cell membrane space with unneeded enzymes. There were no differences in aminopeptidase-N, trypsin, or chymotrypsin activities between species with different percent protein in their diets. However, consistent with the adaptive modulation hypothesis, we found that species with a higher percent starch in their diets had higher maltase, sucrose, and amylase activities. However, future studies may need to be conducted to differentiate long-term, evolutionary matching from rapid modulation of enzyme levels.
28 p.
Keywords: Forest and Wildlife Ecology